PENGARUH CITRA MEREK TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI MEDIASI PADA PRODUK VIVA KOSMETIK DI KOTA SURABAYA - ANGGRAENI, PRISKA NITA (Universitas Katolik Widya Mandala Surabaya, 2013)
This research aim to analyze the effect of brand image and customer loyalty with customer satisfaction as a mediates at Viva cosmetic products in Surabaya. This research uses SEM (Structural Equation Modeling), and sampling technique used in this research was non-probability sampling technique with using 100 repondents. Characteristics responden of the study of were women aged 18-55 years with domiciled in the city of Surabaya, has a job and use the Viva Cosmetic products. The results of this study indicate that there are significant functional benefits and the symbolic benefit to customer satisfaction and customer loyalty. The results also indicate that there are significant customer satisfaction to customer loyalty and show that there are significant consumer satisfaction as a mediating variable between functional benefits and symbolic benefits of consumer loyalty.